Epidemiology and risk factors for mortality in clostridial bacteremia in Japan: A retrospective multicenter observational study - Aiko Okazaki; Shu Okugawa; Tatsuya Kobayashi; Miki Kawada; Kyotaro Kawase; Shin Nakayama; Yoshitaka Wakabayashi; Takatoshi Kitazawa; Riko Takezawa; Keita Tatsuno; Saho Koyano; Yoshimi Higurashi; et al. (International Journal of Infectious Diseases)
ABSTRACT: Objectives: Clostridium species are ubiquitous in nature and commonly cause infections, including bacteremia. C. perfringens is often the causative species, while the epidemiology of other clostridial species remains unclear. This study aimed to examine the epidemiology and risk factors for mortality among patients with clostridial bacteremia in Japan. Methods: This multicenter, retrospective cohort study analyzed patients with Clostridium spp. in blood cultures from four tertiary hospitals in Japan. Data on demographics, underlying conditions, clinical and laboratory values, and in-hospital mortality were included. Multivariate logistic regression analysis identified independent risk factors for in-hospital mortality. Results: Of 349 patients with Clostridium spp. in blood cultures, 278 (79.7%) had clinically significant clostridial bacteremia: C. perfringens was the most common species (52.9%), followed by C. ramosum (9.7%) and C. clostridioforme (4.3%). The median patient age was 77 years, and 61.9% were male. The in-hospital mortality rate was 25.9%, with 34.7% of deaths occurring within 3 days of the date of the positive blood culture. Independent risk factors for mortality were hepato-pancreato-biliary malignancy, chronic heart failure, acute renal failure, Pitt bacteremia score, and pneumonia. Conclusions: Mortality from clostridial bacteremia is high, particularly among patients with pneumonia, comorbidities, or severe acute conditions. To improve mortality, early-stage treatment strategies are needed.